Racial/ethnic differences in treatment recommendations: lifestyle changes and medication prescriptions for high cholesterol. Issue 2 (17th February 2020) - Bacon, Emily
ABSTRACT: Objective: High cholesterol is a common condition in the United States, affecting nearly one third of adults, and is a leading precursor to coronary heart disease. This study investigates race/ethnic differences in treatment recommendations for patients with high cholesterol, including prescription medication and lifestyle changes such as eating less fat, losing weight, or exercising more. Design: Data were obtained from the 2005 to 2010 National Health and Nutrition Examination Survey ( N  = 4846), a representative sample of adults in the United States, and the 2005–2010 National Ambulatory Medical Care Survey ( N  = 12, 113), a representative sample of patient visits in the United States. Logistic regression analyses were used to assess whether health professionals recommended lifestyle changes or medication prescriptions differently by patient race/ethnicity and age. Models adjusted for demographic characteristics, socioeconomic status, health behaviors, health care access/utilization, and comorbidities. Results: Non-Hispanic Black and Hispanic patients with high cholesterol were significantly and substantially more likely to receive recommendations for lifestyle changes compared to non-Hispanic White patients. These differences were exacerbated at younger ages and largely diminished for adults over the age of 65. These patterns were reflected in both datasets. However, non-Hispanic Black patients from the NHANES analysis were less likely than non-Hispanic White patients to receive medication prescriptions for high cholesterol, particularly at younger ages. There were no race/ethnic differences in odds of medication prescriptions for Hispanic patients compared to White patients. Conclusions: Results suggest widespread and pervasive race/ethnic differences in recommending lifestyle changes for patients with high cholesterol. Although lifestyle changes may lower cholesterol they are often less effective than prescription medication. Because differences in lifestyle recommendations were not reflected in prescription practices, results may indicate a form of discrimination within physician-patient interactions that could be addressed by increased provider education about most effective treatment practices.